1997
DOI: 10.1007/s004110050064
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality in Bavaria, Germany, after the Chernobyl reactor accident

Abstract: As has been shown by the authors of a paper recently published in this journal, a deviation from a long-term trend in perinatal mortality within the former Federal Republic of Germany occurred in 1987, i.e. 1 year following the Chernobyl disaster. It is the aim of this study to make a comparison between the areas of the state Bavaria. Germany, with different fallout levels as well as between the observed and expected numbers of perinatal deaths relating to these areas. The expected numbers of perinatal deaths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
0
18
0
1
Order By: Relevance
“…Our results are also consistent with those of the Childhood Cancer Survivor Study, which included 4,029 pregnancies; 37 of those pregnancies ended in a stillbirth (18). Up to now, studies regarding the consequences of the Chernobyl accident have been less informative because they are only temporal trend studies without individual dose estimations: An increased risk of stillbirths was found in some Eastern European countries during a period starting 1 mo after the Chernobyl accident and ending 2 y thereafter, but the results were considered by the authors to be inconsistent with the low level of effective radiation doses received by these populations (0.1-0.2 mSv/y) (19). Similar results for similar dose levels were found in Bavaria and throughout Germany during the year after the accident, but total infant mortality gradually decreased during the same period (19)(20)(21).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our results are also consistent with those of the Childhood Cancer Survivor Study, which included 4,029 pregnancies; 37 of those pregnancies ended in a stillbirth (18). Up to now, studies regarding the consequences of the Chernobyl accident have been less informative because they are only temporal trend studies without individual dose estimations: An increased risk of stillbirths was found in some Eastern European countries during a period starting 1 mo after the Chernobyl accident and ending 2 y thereafter, but the results were considered by the authors to be inconsistent with the low level of effective radiation doses received by these populations (0.1-0.2 mSv/y) (19). Similar results for similar dose levels were found in Bavaria and throughout Germany during the year after the accident, but total infant mortality gradually decreased during the same period (19)(20)(21).…”
Section: Discussionmentioning
confidence: 53%
“…Up to now, studies regarding the consequences of the Chernobyl accident have been less informative because they are only temporal trend studies without individual dose estimations: An increased risk of stillbirths was found in some Eastern European countries during a period starting 1 mo after the Chernobyl accident and ending 2 y thereafter, but the results were considered by the authors to be inconsistent with the low level of effective radiation doses received by these populations (0.1-0.2 mSv/y) (19). Similar results for similar dose levels were found in Bavaria and throughout Germany during the year after the accident, but total infant mortality gradually decreased during the same period (19)(20)(21). In contrast to but consistent with the Japanese atomic bomb survivor results, the stillbirth rate appeared to be unaffected by the Chernobyl accident in Finland, despite a welldocumented monthly dose estimation (22), in Sweden (23), and in Norway (24).…”
Section: Discussionmentioning
confidence: 53%
“…However, a more detailed analysis did not find differences according to fallout level in Bavaria, the most heavily contaminated part of the former Federal Republic of Germany (34).…”
Section: Discussionmentioning
confidence: 69%
“…5% Körblein, 2003;Scherb and Weigelt, 2003;Frentzel-Beyme and Scherb, 2007;Norway Ulstein et al, 1990 Hungary Czeizel andBillege, 1988;Scherb and Weigelt, 2003 Finland Increased ca. 20% Harjulehto et al, 198920% Harjulehto et al, , 1991Scherb and Weigelt, 2003;Frentzel-Beyme andScherb, 2007 Germany Körblein andKüchenhoff, 1997;Scherb and Weigelt, 2003;Lüning et al, 1989;Grosche et al, 1997;Scherb et al, 1999;Körblein, 2003a;Frentzel-Beyme and Scherb, 2007England and Wales Increased twofold in February 1987Bentham, 1991Busby, 1995 Denmark Increased 20% Frentzel-Beyme and Scherb, 2007 Iceland Increased 30% Frentzel-Beyme and Scherb, 2007 Hungary Increased 30% Frentzel-Beyme and Scherb, 2007 long-term trend. Infant mortality monthly data, 1985-1991, show a significant correlation with the Cs-137 burden during pregnancy (Körblein, 2003(Körblein, , 2006.…”
Section: Russiamentioning
confidence: 97%